Effect of Quercetin, Caffeic Acid and Caffeic Acid Phenylethyl Ester, Solubilized in Non-ionic Surfactants, on Histamine Release in vivo and in vitro - Scheller, Stan; Dworniczak, Szymon; Pogorzelska, Teresa; Rajca, Marek; Shani, Jashovam (Arzneimittelforschung, 2000)
A practical hindrance in using many therapeutic agents is their limited solubility in aqueous matrixes. This is usually overcome by incorporating the active compounds in a matrix, with the aid of a non-ionic surfactant. Three water-insoluble natural polyphenols with inherent biological activity, quercetin (CAS 117-39-5), caffeic acid and caffeic acid phenylethyl ester, were solubilized in water, with the aid of Tween®. 80 (an esterified and polyethoxylated derivative of sorbitan), Solutol®. HS15 (a polyethoxylated derivative of 12-hydroxy-stearic acid), Cremophor®. RH40 (a ricinoleic acid derivative) or Cremophor®. EL and the effect of the solubilized polyphenols on histamine release was studied in vitro (mast cells) and in vivo in the rat.In vivo Cremophor EL alone increased, and Tween 80 decreased histamine plasma levels. All four groups injected with solubilized quercetin exhibited a decrease in their plasma histamine levels. Caffeic acid solubilized in Cremophor RH40 decreased histamine levels, too. In vitro Tween 80 increased histamine release in a dose-dependent mode. Quercetin in vitro inhibited histamine release in all solubilizers used.It is concluded that the ability of the studied polyphenols to release histamine is not only depending on the condition of the storage vesicles in the mast cells, but also on the surfactant used to solubilize them.
Keywords: Caffeic acid; Caffeic acid phenylethyl ester; Cremophor EL; Cremophor RH40; Histamine release; Mast cells; Quercetin; Solutol HS15; Surfactants; Tween 80